EFL Students’ Perceptions of Google Docs Feedback in Folktale Translation Revision: A Narrative Inquiry - Hemalia Putri Johar Manik; Ellisa Indriyani Putri Handayani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Feedback plays an essential role in helping students improve translation quality, particularly in digitally mediated learning environments. Although previous studies have widely examined digital feedback in academic writing, limited research has explored how EFL students perceive and use feedback in Google Docs when revising culturally rich texts, such as folktale translations. Addressing this gap, this study investigates EFL undergraduate students’ perceptions of Google Docs feedback in folktale translation revision through a narrative inquiry approach. The study involved three undergraduate students enrolled in a translation course at a state university in Central Java, Indonesia. Data were collected through narrative frames, semi-structured interviews, and artifact documentation, and analyzed using thematic narrative analysis. The findings reveal that students perceive Google Docs feedback as an essential support for improving translation quality, particularly in lexical choices, clarification of meaning, and culturally appropriate translation decisions. The study also indicates that students respond to feedback cognitively, affectively, and conatively in different ways depending on the clarity of the feedback, emotional readiness, and level of participation in collaborative revision. In addition, students encountered several challenges, including difficulties understanding indirect feedback, selecting culturally equivalent expressions, managing workload and time constraints, and dealing with technical issues in online collaboration. This study contributes to the growing discussion on digital feedback literacy in translation learning by demonstrating how students interpret and apply feedback during translation revision in collaborative digital environments.